Analysis Of The Realization of the 2023 Regional Revenue and Expenditure Budget at the Regional Revenue Agency of Nabire Regency - Petonengan, Meidi; Baharuddin, Baharuddin; Malisa, Mika (Institut Manajemen Wiyata Indonesia, 2025)
The Regional Revenue Agency (Bapenda) of Nabire Regency plays a strategic role in supporting the Regent in administering regional government affairs, particularly in the field of revenue management. This study aims to analyze the realization of the 2023 Regional Revenue and Expenditure Budget (APBD) at the Regional Revenue Agency of Nabire Regency. Employing a qualitative research approach, the study was conducted at Bapenda Nabire Regency using both primary and secondary data sources. Data were collected through observation, in-depth interviews with four financial officers, and documentation review. Data analysis was carried out descriptively through the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that regional revenue realization in the 2023 APBD reached Rp 46,924,222,592.00, equivalent to 157% of the targeted revenue, demonstrating the effectiveness of tax collection strategies, particularly in Land and Building Tax (PBB) and Land and Building Rights Acquisition Duty (BPHTB). Meanwhile, expenditure realization reached 98%, reflecting efficient and accountable budget utilization. These achievements were supported by increasing taxpayer awareness and improved service quality, although challenges related to human resource capacity and budget limitations remain. The realization of revenue and expenditure is influenced by several factors, including the quality of human resources, budget availability, implementation of standard operating procedures, taxpayer awareness, and the ease of payment systems. Overall, effective budget realization contributes positively to regional development by enhancing community welfare, promoting economic growth, strengthening regional fiscal independence, and reducing dependence on external funding sources.